Understanding the impact of microstructure on the response of titanium alloys to aging treatments - Callegari, Bruna (2020)
The impact of the initial microstructure on the behavior of the β-metastable alloy Ti-5Al-5Mo-5V-3Cr (Ti-5553, composition in wt%) and the α+β alloy Ti-6Al-4V (Ti-64, composition in wt%) during subsequent isothermal treatments has been evaluated in this work. Thermal and thermomechanical treatments were imposed to the alloys to achieve such microstructural variability. Regarding Ti-5553, it was concluded that the β phase undergoes dynamic recovery above and below its β-transus temperature, and recovery is more dominant at lower strain rates. Meanwhile, α phase undergoes not only a process of breakage and globularization, but also decomposition, which contributes to flow softening. The increase in strain rate caused non-uniform recovery in the β field and a more intense refinement of α precipitates in the α+β field. Macrotexture evaluation after deformation indicates that β\'s texture is much stronger than that of α, with its (200) component being the strongest one. Relevant microstructures were then selected to undergo aging treatments. Results show that the presence of deformation-induced defects accelerates phase precipitation during aging, and that the composition of the β matrix, which is affected by the amount of primary α, plays a major role. The α\'\' phase tends to form from the β matrix in high quantities without the presence of primary α phase or with a low fraction of this phase, and the conversion of α\'\' into α is sluggish, being faster in the β-heat-treated condition, whereas a continuous β → α transformation occurs, with little or no precipitation of α\'\' in the α+β-heat-treated condition. With respect to Ti-64, during deformation in the β field, lower strain rates appear to cause a decrease in the aspect ratio and in the c/a ratio of final martensitic laths and an increase in the final amount of retained β phase. Lower strain rates during deformation in the α+β field also increase the β phase fraction. However, an excessive amount of β causes its instability during quenching, with consequent transformation into secondary α. At a lower temperature in the α+β field, the globularization tendency of the alloy is significantly enhanced, especially during slow deformation. Significant fiber texture of the α/α\' phase was observed only after deformation in the β field. Grain orientation spread analyses have shown a high degree of internal misorientation in deformed α lamellae and the tendency of globularization of lamellae by the evolution of internal low angle boundaries to high angle boundaries. Conditions of interest were chosen for aging treatments. Results show that β decomposition into fine secondary α laths, transformation of the metastable martensitic α\' into the equilibrium α phase and precipitation of the intermetallic Ti3Al can take place during aging. The composition and distribution of the β phase was shown to affect the precipitation of secondary α during aging, while the composition of the α phase plays a key role on the formation of Ti3Al. In situ X-ray diffraction studies indicate the contribution to hardening by the increase of the c/a ratio during the α\' → α conversion and the chemical homogenization of the β phase.